Pengaruh Promosi Media Online, Persepsi Harga Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada Aplikasi Shopee (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Jurusan Manajemen Universitas Islam Malang ) - Astutik, Helmi; Nurhajati, Nurhajati; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the influence of Online Media Promotion, Price Perceptions, and Consumer Trust on Purchasing Decisions on the Shopee application (Case study of Students from the Faculty of Economics and Business, Department of Management, Islamic University of Malang). The method used is a survey using a questionnaire as a data collection instrument. The research sample consisted of 82 respondents who were active users of the Shopee application and had made purchases on the Shopee application. The results of this research show that the influence of Online Media Promotion, Price Perception, and Consumer Trust simultaneously have a positive and significant effect on Purchasing Decisions on the Shopee application. There is a positive and significant influence between the Online Media Promotion variable on Purchasing Decisions on the Shopee application. The Price Perception variable does not have a significant effect on Purchasing Decisions on the Shopee application. There is a positive and significant influence between the Consumer Trust variable on Purchasing Decisions on the Shopee application.  Keywords: Online Media Promotion, Price Perceptions, Consumer Trust, Purchase Decision